Exploring the Influence of Child/Race Ethnicity and Child Maltreatment Type on Teacher Reporting Intention - Glouchkow, Amanda (Université d'Ottawa | University of Ottawa, 2025)
Despite Canadian teachers being the most frequent reporters to child welfare agencies, research shows many teachers who suspect child maltreatment fail to make a report. In this research study, we aimed to advance the understanding of various levels of influence (i.e., teacher and system characteristics) as well as the impact of components from the theory of planned behaviour on teachers’ child maltreatment reporting intentions. Canadian teachers (N = 93) viewed case vignettes that varied across maltreatment types (sexual, physical, emotional abuse, neglect, intimate partner violence (IPV) exposure) and child race/ethnicity (Black, White, Indigenous, East Indian, Chinese) and indicated the likelihood of reporting each case vignette within the factorial survey design. They also responded to questions related to the teacher and system characteristics, including theory of planned behaviour components. Findings showed a significant difference in teachers’ reporting intentions based on teacher and system characteristics, although the influence fluctuated based on the two manipulated variables. Reporting intentions were highest for sexual abuse, followed equally by physical abuse and IPV exposure, and then neglect and emotional abuse. Legal obligations and a desire to help drove reporting, while fears of worsening circumstances and resource suitability hindered it. Race/ethnicity had no direct effect, but subjective norms increased reporting likelihood for Black, East Indian, and Chinese children. The results highlight the need for a comprehensive understanding of multi-level predictors of teachers’ child maltreatment reporting intentions and how they fluctuate based on type of maltreatment and race/ethnicity of the child victim.
Keywords: Child; Maltreatment; Reporting; Teachers